Imbalance of Circulatory T Follicular Helper and T Follicular Regulatory Cells in Patients with ANCA-Associated Vasculitis - Xu, Ying; Xu, Hongmei; Zhen, Yu; Sang, Xueting; Wu, Hao; Hu, Cong; Ma, Zhanchuan; Yu, Miaomiao; Yi, Huanfa (Mediators of Inflammation, 2019)
Antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV) is characterized by small-vessel inflammation in association with autoantibodies. Balance between T follicular helper (Tfh) cells and T follicular regulatory (Tfr) cells is critical for humoral immune responses. Accumulating evidence supports that Tfh and Tfr are involved in autoimmune diseases; however, their roles in AAV are unclear. In this study, we tested the changes of circulatory Tfh and Tfr in patients with AAV. Twenty patients with AAV and twenty healthy controls were enrolled. Sixteen AAV patients had kidney involvement. We found that the AAV patients had increased circulating Tfh cells (CD4+CXCR5+CD25−CD127interm-hi), decreased Tfr cells (CD4+CXCR5+CD25+CD127lo-interm), and elevated Tfh/Tfr ratios compared with healthy controls (P<0.01). The Tfh percentage and Tfh/Tfr ratio, but not Tfr percentage, were positively correlated to proteinuria levels and BVAS scores in patients with AAV (P<0.01). In addition, AAV patients had decreased circulating Tfh1 (CCR6-CXCR3+), but increased Tfh2 cells (CCR6-CXCR3-), compared with healthy controls (P<0.01), indicating a Tfh1-to-Tfh2 shift. Furthermore, remission achieved by immunosuppressive treatment markedly attenuated the increase of total Tfh (P<0.01) and Tfh2 cells (P<0.05), promoted the Tfh1 response (P<0.05), and recovered the balance between Tfh/Tfr cells (P<0.05) and between Tfh1/Tfh2 cells (P<0.05) in patients with AAV. Plasma levels of IL-21, a cytokine secreted by Tfh cells, were elevated in AAV patients compared with healthy controls (P<0.01), which was attenuated by immunosuppressive treatment (P<0.05). Taken together, our findings indicate that circulatory Tfh/Tfr ratios, Tfh2/Tfh1 shift, and plasma IL-21 levels are associated with AAV and disease activity.